2021
DOI: 10.1136/jitc-2021-002997
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor from Colleet al

Abstract: In their article, Fucà et al highlight that early tumor shrinkage and depth of response predict the prognosis of patients with metastatic colorectal cancer (mCRC) microsatellite instability (MSI-H)/deficient mismatch repair (dMMR) treated by immune checkpoint inhibitors (ICI). We are surprised that no cases of pseudoprogression (PSPD) were reported in their study. PSPDs were described under ICI in patients treated for MSI/dMMR mCRC. In a cohort of 123 patients treated with anti-PD1±antiCTL-4 for MSI/dMMR mCRC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We read with interest the letter from Colle et al 1 highlighting the lack of pseudoprogression (PSPD) events reported in our study on the prognostic impact of the radiological tumor response dynamics in patients with microsatellite instability-high/deficient mismatch repair (MSI-H/dMMR) metastatic colorectal cancer (mCRC) receiving immune checkpoint inhibitors (ICIs). 2 Our patients discontinued ICIs immediately after the evidence of progressive disease (PD) and, in most of the cases, the radiological PD was paralleled by the worsening of their clinical conditions, especially for heavily pretreated patients with primary PD.…”
Section: Dear Editormentioning
confidence: 92%
“…We read with interest the letter from Colle et al 1 highlighting the lack of pseudoprogression (PSPD) events reported in our study on the prognostic impact of the radiological tumor response dynamics in patients with microsatellite instability-high/deficient mismatch repair (MSI-H/dMMR) metastatic colorectal cancer (mCRC) receiving immune checkpoint inhibitors (ICIs). 2 Our patients discontinued ICIs immediately after the evidence of progressive disease (PD) and, in most of the cases, the radiological PD was paralleled by the worsening of their clinical conditions, especially for heavily pretreated patients with primary PD.…”
Section: Dear Editormentioning
confidence: 92%